R&D-driven biases in energy-saving technical change: A putty-practically-clay approach - Adriaan van Zon; Thomas S. Lontzek (Kiel Institute for the World Economy (IfW), 2008)
This paper deals with the problem of tackling the adverse effect of output growth on environmental quality. For this purpose we use an intermediate sector that builds putty-practically-clay capital consisting of an amalgam of energy and raw capital used for final goods production. The putty-practically-clay model is a strongly simplified version of a full putty-clay model, that mimics all the relevant behaviour of a full putty-clay model, but that does not entail the administrative complications of a full putty-clay model. In addition, we introduce an R&D sector that develops renewable and conventional energy-related technologies. The allocation of R&D activities over these two uses of R&D gives rise to an induced bias in technical change in line with Kennedy (1964). In the context of our model, this implies that technological progress is primarily driven by the desire to counteract the upward pressure on production cost implied by a continuing price increase of conventional energy resources. By means of illustrative model simulations we study the effects of energy policy on the dynamics of the model for alternative policy options aimed at achieving Greenhouse Gas emission reductions. We identify the conditions under which energy policy might partly backfire and present some non-standard policy implications.
Keywords: E22; O31; O33; Q42; Q48; 330; Induced biased technological change; putty-clay vintage models; energy; renewable resources; Putty-Clay-Modell; Forschung; Regenerative Energie; Energiesparen; Technischer Fortschritt; Energiepolitik; Klimaschutz; Theorie